Epoxycarotenoid‐mediated synthesis of abscisic acid in Physcomitrella patens implicating conserved mechanisms for acclimation to hyperosmosis in embryophytes. Issue 1 (24th December 2014) - Takezawa, Daisuke; Watanabe, Naoki; Ghosh, Totan Kumar; Saruhashi, Masashi; Suzuki, Atsushi; Ishiyama, Kanako; Somemiya, Shinnosuke; Kobayashi, Masatomo; Sakata, Yoichi
Summary: Plants acclimate to environmental stress signals such as cold, drought and hypersalinity, and provoke internal protective mechanisms. Abscisic acid (ABA), a carotenoid‐derived phytohormone, which increases in response to the stress signals above, has been suggested to play a key role in the acclimation process in angiosperms, but the role of ABA in basal land plants such as mosses, including its biosynthetic pathways, has not been clarified. Targeted gene disruption of PpABA1, encoding zeaxanthin epoxidase in the moss Physcomitrella patens was conducted to determine the role of endogenous ABA in acclimation processes in mosses. The generated ppaba1 plants were found to accumulate only a small amount of endogenous ABA. The ppaba1 plants showed reduced osmotic acclimation capacity in correlation with reduced dehydration tolerance and accumulation of late embryogenesis abundant proteins. By contrast, cold‐induced freezing tolerance was less affected in ppaba1, indicating that endogenous ABA does not play a major role in the regulation of cold acclimation in the moss. Our results suggest that the mechanisms for osmotic acclimation mediated by carotenoid‐derived synthesis of ABA are conserved in embryophytes and that acquisition of the mechanisms played a crucial role in terrestrial adaptation and colonization by land plant ancestors. Abstract : See also the Commentary by Cuming and Stevenson